Ameliorative effect of gallic acid in paclitaxel-induced neuropathic pain in mice. (2019) - Kaur, Satbir; Muthuraman, Arunachalam
Graphical abstract: Highlights: Gallic acid (GA) is a natural phenolic type of neuroprotective compound. GA possesses anti-nociceptive action against paclitaxel-induced neurotoxicity. GA inhibits THF-α mediated neuropathic pain sensation. Abstract: The present study has been investigated the role of gallic acid (GA) in paclitaxel-induced neuropathic pain. The neuropathic pain was developed with paclitaxel (PT: 2 mg/kg, i.p. ) administration in mice. GA (20 and 40 mg/kg) and pregabalin (PreG: 5 mg/kg) were administered intravenously for 10 consecutive days. The neuralgic sensations were investigated by assessing various pain tests like acetone drop, pinprick, plantar, tail flick, and tail pinch test. Mice pain behaviors were evaluated on 0, 4 th, 8 th, 12 th and 16 th days. The levels of sciatic nerve thiobarbituric acid reactive substances (TBARS), reduced glutathione (GSH), superoxide anion, calcium, myeloperoxidase (MPO), and TNF-α were estimated. Treatment of GA and PreG attenuate PT induced thermal &mechanical hyperalgesia and allodynia symptoms along with the reduction of TBARS, total calcium, TNF-α, superoxide anion, and MPO activity levels; and decreased GSH level. Therefore, it has been concluded that GA has potential neuroprotective actions against PT induced neuropathic pain due to it's anti-oxidant, anti-inflammation and regulation of intracellular calcium ion concentration.